O processo de alfabetização e letramento na transição da educação infantil para o ensino fundamental no município de São Carlos/SP - Artussa, Lucimara (2020)
This master's dissertation is linked to the research line State, Politics and Human Training, of the Postgraduate Program in Education - PPGE / UFSCar, under the guidance of Professor Maria Iolanda Monteiro. The research topics investigated are literacy and literacy, such as Public Policies for literacy and literacy with a focus on the first year of elementary school and elementary school and teaching reading and writing in the last stage of early childhood education. It is adopted as a research problem or process of literacy and transition in Early Childhood Education for the Elementary Education of Nine Years in the Education of the Teacher of São Carlos / SP and Public Policies for Basic Education and as General General process of literacy and transition in the last stage of Early Childhood Education for the first year of Elementary Education of Nine Years from the perspective of Public Policies for Basic Education and the conceptions of teachers who study these first two teaching classes in São Carlos / SP. It consists of qualitative research, Bogdan; Biklen, 2010; Ludke; André, 2014, in the form of a case study, which featured semi-structured interviews from four public schools in the municipality of São Carlos / SP, two teachers with experience in the last stage of Early Childhood Education and two with experience in the first year of elementary school for new years. A documentary analysis was also carried out, with the reading of the Pedagogical Political Project - PPP of the schools and the reading of documents of an official nature, including laws, decrees and opinions, with emphasis on the National Pact for Literacy in the Right Age - PNAIC and the Base National Common Curriculum - BNCC. For the analysis of the data, four axes of analysis were defined: Conceptions about literacy and literacy; Oral reports on teaching practices with reading and writing; Knowledge about Public Policies; and Conceptions about the transition from the last stage of Early Childhood Education to the first year of Elementary School. The reflections raised from the results are that thinking about literacy and literacy in this moment of the child's transition from one stage to another, is not thinking about anticipating the first year, transporting him to the Early Childhood Education room. The image of literacy does not have to be that of a small child suffering, leaning in front of an exhaustive page containing successive copies of the same word. It can be reinvented from early childhood education, without suffering or punishment for children, but that they can live literacy and literacy from an early age, building, from learning to learning, their path of success in acquiring reading techniques, writing and interpretation, autonomously interacting with the most diverse textual genres in their daily lives. In addition, teaching work, regardless of whether it is in Early Childhood Education or Elementary Education, requires a deepening of the different types of knowledge. It is not possible to support teaching only in practice, without failing to know the Public Policies involved in the pedagogical work and the consultation of different theoretical references that may support the pedagogical practice.